European Union social policy for the elderly - Czapulis-Rutkowska, Zofia (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Recent decades have witnessed tendency to deepen integration within European Union. The reason for this is understanding that more integrated Europe will be more able to face the growing challenges of globalization, competitiveness and population aging. In this context the need emerges to harmonize member states' social policy in general and social policy connected with the elderly, in particular. European Union is formulating goals for social policy in the field of pensions and also in the field of long term care. European Union strongly promotes the minimum standard of living for the elderly, whereas additional part allowing for continuation of previous standard of living may be secured by the private or occupational institutions. Social policy is still in the competence of the member states therefore it is difficult to implement corresponding to the mentioned above goals, policy at supranational level.